The influence of organizational climate, organizational culture and work environment on the performance of social service employees of Central Kalimantan province - Anike Retawati; Hansly Tunjang (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine the effect of organizational climate, organizational culture, work environment on the performance of Social Service Employees of Central Kalimantan Province. It is important to improve the performance that has a positive impact on the independent variable, so that a quantitative test is carried out. The method of this research is this type of research is descriptive and quantitative with the SPSS 22.0 analysis tool. The results of the research are to provide information on research problems, and at the same time link the formulation, benefits in the research hypothesis as causation used to answer statements from the questionnaire. The type of sample data is primary data with a questionnaire of 51 people, Social Service employees. The results of research on organizational climate, organizational culture, work environment on employee performance have a significant positive effect of 63% on employee performance. This means that the higher the independent role of organizational climate, organizational culture, work environment, the better the performance of employees. The results provide implications, to pay more attention to organizational climate, organizational culture, work environment on employee performance. For further research, we can examine the variables of participatory leadership style.